2003
DOI: 10.1037/1524-9220.4.2.91
|View full text |Cite
|
Sign up to set email alerts
|

A multicultural investigation of masculinity ideology and alexithymia.

Abstract: The aims of this study were to investigate the social constructionist proposition that masculinity varies according to social context and the relationship, in men, between masculinity ideology and alexithymia. Women tended to endorse a less traditional view of masculinity than did men, and European Americans tended to endorse a less traditional view of masculinity than did African Americans, with Hispanics from the Caribbean and the United States in the middle. A relationship between masculinity ideology and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 22 publications
6
128
1
1
Order By: Relevance
“…Black men (Levant, Majors, & Kelley, 1998) and Black and Latino men (Levant et al, 2003). A consistent finding among these studies is that men and racial-ethnic minorities tend to report higher levels of TMI compared to women and individuals from the racial-ethnic majority (c.f., Levant & Richmond, 2016).…”
Section: Indeed Investigators Have Examined Different Versions Of Thsupporting
confidence: 67%
“…Black men (Levant, Majors, & Kelley, 1998) and Black and Latino men (Levant et al, 2003). A consistent finding among these studies is that men and racial-ethnic minorities tend to report higher levels of TMI compared to women and individuals from the racial-ethnic majority (c.f., Levant & Richmond, 2016).…”
Section: Indeed Investigators Have Examined Different Versions Of Thsupporting
confidence: 67%
“…Black men often express their masculinity in a "cool pose," which emphasizes pride, strength, and control (Majors & Billson, 1992, p. 4). Latino and African American cultures emphasize the most traditional views of masculinity (Levant et al, 2003), putting more pressure on men from these groups to conform. Having received the brunt of aggression and power in the role of victim, one trajectory taken by a minority but significant number of abused men is to react by becoming hypermasculine; in other words, hyperaggressive, overcontrolled, unemotional, action oriented, and abusive to others (Gartner, 1999;Lisak, 1995).…”
Section: Masculinity and Childhood Sexual Abusementioning
confidence: 99%
“…Findings confirmed the hypothesis that female participants were less likely than male participants to endorse a culturally traditional sense of masculinity. Levant et al (2003) also found that African American women were more likely to identify with and endorse a more traditional sense of masculinity, whereas European American women were least likely, with Hispanic women in the middle. Additionally, both African American and Hispanic men were more likely than European American men to endorse more traditional ideals of masculinity.…”
Section: Perception Of Gender Rolesmentioning
confidence: 85%
“…Additionally, both African American and Hispanic men were more likely than European American men to endorse more traditional ideals of masculinity. Levant et al (2003) claimed that there was little variability between cultures in the perception of masculinity ideologies, with alexithymia (inability or difficulty to identify one's emotions) consistently being paired with a more "traditional" sense of masculinity. This suggests that in fitting with masculine norms a man may be encouraged to disconnect from his emotions.…”
Section: Perception Of Gender Rolesmentioning
confidence: 99%
See 1 more Smart Citation